Generalized logistic growth modeling of the COVID-19 pandemic in Asia - Elinor Aviv-Sharon; Asaph Aharoni (Infectious Disease Modelling, 2020)
Several months into the ongoing novel coronavirus disease 2019 (COVID-19) pandemic, this work provides a simple and direct projection of the outbreak spreading potential and the pandemic cessation dates in Chinese mainland, Iran, the Philippines and Taiwan, using the generalized logistic model (GLM). The short-term predicted number of cumulative COVID-19 cases matched the confirmed reports of those who were infected across the four countries, and the long-term forecasts were capable to accurately evaluate the spread of the pandemic in Chinese mainland and Taiwan, where control measures such as social distancing were fully implemented and sustained, suggesting GLM as a valuable tool for characterizing the transmission dynamics process and the trajectory of COVID-19 pandemic along with the impact of interventions.